2002
DOI: 10.1038/sj.leu.2402370
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma level of differentiation inhibitory factor nm23-H1 protein correlates with risk factors for myelodysplastic syndrome

Abstract: We measured plasma nm23-H1 level (nm23-H1), a differentiation inhibitory factor, by an enzyme-linked immunosorbent assay (ELISA) in patients with aplastic anemia (AA) and myelodysplastic syndrome (MDS). The nm23-H1 in AA was not significantly elevated when compared to normal subjects (6.66 ± 1.20 ng/ml vs 5.13 ± 0.81 ng/ml; P = 0.274). In contrast, MDS patients had significantly high levels of nm23-H1 compared not only to normal subjects (11.16 ± 1.42 vs 5.13 ± 0.81 ng/ml; P = 0.0004) but also to those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These spots contained proteins associated with cytokinesis (macrophage‐capping protein, and cofilin 1), proliferation (prohibitin), apoptosis (apoptosis‐associated speck‐like protein containing a CARD isoform a), and redox balance (antioxidant PRDX2). A differentiation inhibitory factor, nm23, which was reported to be elevated in the plasma of MDS patients (Ito et al , ), was also identified (data not shown), although only three patients showed increased expression.…”
Section: Resultsmentioning
confidence: 85%
“…These spots contained proteins associated with cytokinesis (macrophage‐capping protein, and cofilin 1), proliferation (prohibitin), apoptosis (apoptosis‐associated speck‐like protein containing a CARD isoform a), and redox balance (antioxidant PRDX2). A differentiation inhibitory factor, nm23, which was reported to be elevated in the plasma of MDS patients (Ito et al , ), was also identified (data not shown), although only three patients showed increased expression.…”
Section: Resultsmentioning
confidence: 85%
“…This was the case for acute myeloid leukemia (Yokoyama et al, 1996;Okabe-Kado et al, 1998;Wakimoto et al, 1998;Yokoyama et al, 1998;Cui et al, 2004), for Hodgkin and non Hodgkin lymphoma (Aryee et al, 1996;Lee et al, 2006), for acute lymphoid leukemia (Koomägi et al, 1998;Ning et al, 2009), for peripheral T-cell lymphoma (Niitsu et al, 2003a;Huang et al, 2006;Niitsu et al, 2011) and for diffuse large B-cell lymphoma (Niitsu et al, 2004). Interestingly, the poor prognosis can be evaluated by ELISA test of the NME1 level in patient sera for Hodgkin lymphoma (Niitsu et al, 2008) and non-Hodgkin lymphoma (Niitsu et al, 2001a;Niitsu et al, 2001b), for acute myeloid leukemia (Niitsu et al, 2000), for myelodysplastic syndrome (Ito et al, 2002), for diffuse large B-cell lymphoma (Niitsu et al, 2004;Niitsu et al, 2006) and for extranodal NK/T-cell lymphoma (Niitsu et al, 2003b). However, Bircan et al (Bircan et al, 2008) reported that the increased NME1 expression was of no prognostic value in a series of Hodgkin and non Hodgkin lymphoma.…”
Section: Notementioning
confidence: 99%